EKSISTENSI GUBERNUR SEBAGAI WAKIL PEMERINTAH PUSAT DI DAERAH - Rahyunir Rauf (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2018)
In the Indonesian national government system is recognized the existence of local government, the region consists of provincial, district and municipal areas. The Provincial Region is headed by a Governor, a Regency area headed by a Regent and a City area headed by a Mayor. Based on Law Number 23 Year 2014 on Regional Government placed the Governor in 2 (two) functions, namely; As Head of Region and As Deputy of Central Government in Region. The governor as the representative of the central government in the regions gained the delegation of authority from the government to carry out central government affairs in the regions. As a representative of the central government in the region the governor carries out the absolute affairs and implements the concurrent governmental affairs which are the authority of the central government and conducts the guidance and supervision of the districts / municipalities in carrying out the concurrent affairs which are the authority of the district / city government. In the implementation of central government affairs in the region it is necessary to have central government representatives in the regions and vertical institutions. Prior to the issuance of Law Number 23 Year 2014 in relation to the Governor as the representative of the central government in the regions is regulated in Law Number 32 Year 2004 regarding regional government and followed up by Government Regulation No. 7 of 2008 on Deconcentration and Co-Administration. In Act No. 23 of 2014 on Regional Government it is stated that the representative of central government in the regions is only given to the Governor, while the Regent / Mayor does not get the authority as a representative of the central government in the region. In carrying out the guidance and supervision on the implementation of government affairs which is the authority of the district / city and the task of assistance by the district / city, the President is assisted by the Governor as the representative of the central government.